Tingkat Kepuasan Pengunjung pada Daya Tarik Ekowisata Mangrove Kampoeng Kepiting di Desa Tuban, Kabupaten Badung Provinsi Bali - TURNIP, ELGA SARI; SURYAWARDANI, I GUSTI AYU OKA; ANGGRENI, I GUSTI AYU AGUNG LIES (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism); Vol.12, No.2, Desember 2023, 2023)
Visitor Satisfaction Level at the Mangrove Attraction of Kampoeng Crab Ecotourism in Tuban Village, Badung Regency, Bali Province.  Mangrove ecotourism Kampoeng Kepiting is an ecotourism formed with the main purpose to introduce the preservation and cultivation of mangrove forest ecosystems. The purpose of this study is 1) to analyze the level of importance (importance) of visitors and destination performance (performance) mangrove ecotourism Kampoeng Kepiting and 2) evaluate the level of visitor satisfaction. The study was carried out in Kampoeng Kepiting Mangrove ecotourism in Tuban Village, Badung regency in December 2021 to February 2022 by distributing questionnaires to 100 respondents who visited Kampoeng Kepiting Mangrove ecotourism. The Data were analyzed using the method of Importance Performance Analysis (IPA) and Customer Satisfaction Index (CSI).The results showed that: 1) the results of IPA (Important Performance Analysis) Analysis were distributed in four quadrants. Quadrant I shows a high level of importance and low performance that has not met the expectations of visitors. Indicators that need to be improved are mangrove scenery, mangrove crab cage cultivation, mangrove tours education, crab seedling release tours, Ticket purchase services and quick response in dealing with complaints and visitor responses. Quadrant II shows a high level of importance and performance according to visitors ' expectations. Indicators that need to be maintained are the availability of food stalls, photo spots, clean public bathrooms, Wifi areas; and promotion through social media. Quadrant III which shows a low level of importance and poor performance. Indicators that need to be improved to improve the performance of ecotourism Mangrove attraction is Crab Restaurant, mangrove tour with traditional boat, access road to ecotourism mangrove Kampoeng Kepiting.